Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Lingkup Kantor Kecamatan Mpunda Kota Bima - Adi Ardiansyah; Jaenab Jaenab (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This research was conducted with the aim to find oud the influence of leardership style on employee performance in the scope of the mpunda sub-district office of the city of bima. The variables used in this research are leadership style as an independent variable and employee performance as the dependent variable. The method used in this research is associative analysis method. The population in this study was 33 people. 16 citi servants, 6 honorary employees, and 11 volunteers. The sampling technique used is saturation sampling. The sample used in this study directly uses the overall population of 33 people. Data analysis techniques used in this study are simple linear regression, simple correlation, coefficient of determination, and hypothesis testing (party t-2 test), using the spss version 16.0 test to determine the effect of leadership style on employee performance in the scope of the mpunda sub-district office bima. The results showed that the leadership style variable had a positive and significant effect on employee performance in the area of ​​the Bima city mpunda sub-district office